Understanding Ninth-Grade Students' Perceptions of English Language Learning Regarding Teaching Methods - Ochoa Orozco, Carlos Mario (Universidad Católica Luis Amigó, 2023)
This study aims to analyze the perceptions of ninth-grade students from a private school in Medellín about the teaching methods used in their English as a foreign language classes. Its main objective was to discover how students perceive and value teaching methods and how they contribute to their learning process. Hence, the qualitative research implemented a hermeneutic-phenomenological approach to the data through a questionnaire, focus group sessions, and reflective text results that highlight the need to adapt teaching methods to students' preferences, as well as the fundamental role that families have in promoting motivation, and commitment during the learning process. These results contribute to a deeper understanding of effective teaching strategies in a foreign language classroom.
Keywords: Teaching methods; Student perceptions; English as a foreign language